Research and Practice in Transition: Improving Support and Advocacy of Transgender Middle School Students - Rebecca K. Lewis; Sabrina F. Sembiante (Middle Grades Review, 2019)
In this essay, our purposes are to inspire particular avenues of future research addressing Transgender students, in middle school in particular, and to inform the professional development of teachers in support of these Transgender youth. In relation to the ways in which research can more authentically represent Transgender identity, we argue for the use of Transgender theory as a guiding framework for research addressing Transgender students, issues, and needs. We also describe the particular affordances of qualitative, ethnographic, and phenomenological studies in capturing the unique and highly personal experiences and realities of Transgender individuals, and specifically, in middle school. We then discuss how schools are structured socially and politically along heteronormative and cisnormative lines, presenting a stumbling block for Transgender rights advocacy in educational contexts. Finally, we review the potential of teachers to be the necessary educational change agents to spur greater understanding of and advocacy for students’ gender inclusivity.
Keywords: Transgender; Middle School; heteronormative; cisnormative; teachers; school policy; research